A Comparative Study on Absorbent Layers of Disposable Nursing Pads Produced from New Generation Fibers. Issue 1 (January 2016) - Özdil, Nilgün; Altaş, Sevda
Nursing pads are generally used by nursing mothers to prevent staining of clothing and decrease skin irritation caused by leaking of milk. The aim of this study is the production of a new and alternative absorbent layer for disposable nursing pads. Mixtures of bamboo viscose, soybean, seaweed-embedded cellulose, and silver fibers with cotton fibers were used as raw materials for the production of absorbent layers. Water absorbency, air permeability, and handle properties of the fibers and blends, and antibacterial activity of the raw materials and silver-added absorbent layer were determined.